Societal Responses to Adult Difficulties in L2 Acquisition: Toward an Evolutionary Perspective on Language Acquisition. (13th February 2013) - Schumann, John H.
Abstract : It is generally accepted that second language (L2) acquisition becomes more difficult as one grows older and that success in adult L2 acquisition is highly variable. Nevertheless, humans in language contact situations have to cope with intergroup communication. This article examines the ways society has responded to this challenge. It describes eleven strategies or workarounds that humans use to deal with this problem: developing lingua francas, forming Sprachbunds, practicing exogenous marriage, undergoing language shift, learning the target language imperfectly, developing a pidgin or creole, shifting the learning burden to children, relying on individual differences in aptitude among learners, developing the art and practice of translation, developing machine translation technology, and providing instruction. The eleven strategies can be understood as involving four broad societal responses to the burden of SLA: to simplify the learning task, to create a simpler language, to leave it to a special set of learners, and to provide special training. Finally, the article offers some speculations about the evolutionary reasons for the difficulties experienced in adult L2 acquisition.